Emergency Situations and the Elderly: A Discussion Paper - I Ketut Andika Priastana; I Kadek Artawan; Siti Fadlilah (Babali Publisher, 2023)
Introduction: This discussion paper aims to explore the unique challenges and considerations regarding emergency situations involving elderly individuals. As the global population continues to age, understanding how to effectively respond to emergencies involving older adults becomes increasingly important. This paper discusses various factors that contribute to the vulnerability of the elderly during emergencies, such as physical limitations, cognitive impairments, social isolation, and existing health conditions. It also addresses strategies for emergency preparedness, response, and recovery that can help mitigate risks and enhance the well-being of older adults during crises. Method: This paper is based on literature research. Databases include ScienceDirect, PubMed, and the EBSCO Cumulative Index of Nursing and Allied Health Literature (CINAHL). Key Issues: The following are the primary implications and key findings related to emergencies involving the elderly: vulnerabilities of the elderly, individualized emergency preparedness, community outreach and education, caregiver and family involvement, specialized healthcare and medical services, psychological support, and long-term recovery and resilience. Conclusion: Recognizing the vulnerabilities of the elderly during emergencies and taking appropriate measures is vital for ensuring their safety. It is important to promote customized preparedness strategies tailored to each individual, raise awareness and educate communities about this issue, involve caregivers and families in the process, offer specialized healthcare and psychological support, and prioritize long-term recovery and resilience efforts.